Report of the 1992 geomagnetic conjugate campaign and the present observation system in Iceland - Ken-ichi Kato; Takayuki Ono; Manabu Kunitake; Natsuo Sato; Thorestein Saemundsson (National Institute of Polar Research, 1993)
The present paper describes the observation system and the maintenance work which the authors performed during the conjugate aurora observation period, from September 1 to October 5,1992. The observation program consisted of observation of visible auroras with an all-sky SIT TV camera, aurora emission (670.5nm and 844.6nm) intensity measurements with a multi channel scanning photometer and ionosphere electron density measurement with a TECmeter that used radio waves transmitted from GPS and NNSS satellites. For the present observation program in 1993,new observation systems have been additionaly facilliated with the all-sky TV, scanning photometer and TECmeter. Maintenance work was performed on the continuous observation system. The main work was to rebuild a VLF antenna, to change induction magnetometer sensors and to remove a fluxgate magnetometer sensor. It is noted that continuous observation systems present several problems including superanuation and difficulty in obtaining spare parts.